1970
DOI: 10.13057/nusbiosci/n080204
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Effect of growing media on seed germination and seedling growth of Aganope heptaphylla (Leguminosae)

Abstract: Abstract. Purwantoro RS. 2016. Effect of growing media on seed germination and seedling growth of Aganope heptaphylla (Leguminosae). Nusantara . This study was carried out to explore the effect of growing media on seed germination and seedling growth of Aganope heptaphylla (L.) Polhill. The research was conducted in the greenhouse of Bogor Botanic Gardens nursery during two months from July to August in 2015. An experiment was carried out employing a completely randomized design with three treatments and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It seemed that M 2 medium containing with more tackifier agent had lower porosity and aeration rate than M 1 medium. According to Purwantoro (2016), media with low porosity and aeration decreased the germination rate. This low germination rate could also be increased by soaking C. pallida seeds in hot water with 60ºC temperature for 30 minutes (Kak et al, 2007).…”
Section: Germination Rate Among Local Species Seedsmentioning
confidence: 99%
“…It seemed that M 2 medium containing with more tackifier agent had lower porosity and aeration rate than M 1 medium. According to Purwantoro (2016), media with low porosity and aeration decreased the germination rate. This low germination rate could also be increased by soaking C. pallida seeds in hot water with 60ºC temperature for 30 minutes (Kak et al, 2007).…”
Section: Germination Rate Among Local Species Seedsmentioning
confidence: 99%
“…Different types of planting media will provide different space for roots to develop (Anthonio et al, 2018), so crown growth will also be different. Purwantoro (2016) also reported that different types of planting media significantly affected the germination and growth of Aganope heptaphylla seedlings. Meanwhile, the planting material type showed a significant effect on the plant height and stem diameter at all testing ages.…”
Section: Resultsmentioning
confidence: 94%
“…The effect of different media types and temperatures on water properties is why these two factors can affect C. ternatea germination. Previous studies highlight different media types for germination of other legume species, such as Albizia niopoides and Aganope heptaphylla (Purwantoro, 2016;Silva et al, 2018).…”
Section: Resultsmentioning
confidence: 99%